Hubungan Lama Pengobatan Dan Jenis Obat Antiepilepsi Dengan Efek Samping Obat Pada Pasien Epilepsi Di Poliklinik Neurologi RSUDZA - Sri Hastuti; Nur Astini; Nova Dian Lestari (Journal of Medical Science, 2022)
Epilepsy is one of the most common neurological diseases that can affect people of all ages, races, social classes, and geographic locations. Epilepsy is caused by abnormal release of neurons in the brain characterized by seizures. Data from the World Health Organization shows that epilepsy accounts for a significant proportion of the world's disease burden, affecting nearly 50 million people worldwide. The goal of management of epilepsy patients is to control seizures and improve quality of life. However, the side effects of antiepileptic drugs can significantly impair quality of life. This study aims to determine the relationship between duration of treatment and types of antiepileptic drugs with side effects of drugs in epilepsy patients at RSUDZA Neurology outpatient clinic. This is an observational analytic study with a cross sectional design. The sample of this study was epileptic patients at RSUDZA Neurology Outpatient Clinic based on inclusion and exclusion criteria with a total of 42 samples. Sampling was carried out from May−September 2022 using a consecutive sampling technique and filling out the Liverpool Adverse Effect Profile (LAEP) questionnaire. Existing research sample data were tabulated and analyzed by univariate analysis to present the frequency and percentage. Spearman's correlation statistical test was used to test the relationship between variables.  The patients consisting of 17 men (40.5%) and 25 women (59.5%). The average length of treatment that respondents had undergone was 52 months, all of whom experienced side effects of antiepileptic drugs. The results of the Spearman's correlation statistical test showed that there was no relationship between the length of treatment and the type of antiepileptic drug with drug side effects in patients diagnosed with epilepsy at RSUDZA Neurology Outpatient Clinic.